To find the center and radius of the circle given by the equation \( x^2 + y^2 - 2x + 22y + 1 = 0 \), we will complete the square for both the \(x\) and \(y\) terms.
-
Start with the original equation: \[ x^2 + y^2 - 2x + 22y + 1 = 0 \]
-
Rearrange it to group the \(x\) and \(y\) terms: \[ (x^2 - 2x) + (y^2 + 22y) + 1 = 0 \]
-
Now, complete the square for \(x\):
- The term \(x^2 - 2x\) can be completed as follows: \[ x^2 - 2x = (x - 1)^2 - 1 \]
-
Next, complete the square for \(y\):
- The term \(y^2 + 22y\) can be completed as follows: \[ y^2 + 22y = (y + 11)^2 - 121 \]
-
Substitute back into the equation: \[ ((x - 1)^2 - 1) + ((y + 11)^2 - 121) + 1 = 0 \] Simplifying this: \[ (x - 1)^2 + (y + 11)^2 - 121 = 0 \] \[ (x - 1)^2 + (y + 11)^2 = 121 \]
-
This equation is in the standard form of a circle \((x - h)^2 + (y - k)^2 = r^2\), where \((h, k)\) is the center and \(r\) is the radius.
From this, we can determine:
- Center: \((1, -11)\)
- Radius: \(\sqrt{121} = 11\)
Thus, the answer is: center=(1,−11), radius=11.